Peningkatan Kompetensi Digital Akuntansi Melalui Pelatihan Zahir Accounting Bagi Siswa dan Guru SMK Dharma Loka Pekanbaru - Alfiati Silfi; Eka Hariyani; Meilda Wiguna; Pipin Kurnia; Arumega Zarefar; Rosmayani Rosmayani (CANANG: Jurnal Pengabdian Masyarakat, 2026)
Advances in information technology have driven the transformation of accounting practices from manual to computerized systems. This situation demands that Vocational High School (SMK) graduates possess digital accounting competencies that meet the needs of the business and industrial world. However, students and teachers still lack understanding and skills in using accounting software, necessitating competency improvement through structured training. This community service activity aims to improve the digital accounting competency of students and teachers at SMK Dharma Loka Pekanbaru through training in the use of the Zahir Accounting application. The implementation method includes preparation, training, hands-on practice, mentoring, and evaluation. The material provided includes an introduction to Zahir Accounting, creating company data, managing financial transactions, preparing financial reports, and utilizing the application's supporting features. The training is conducted using lectures, demonstrations, practice, and interactive discussions to ensure participants are able to operate the application independently. The expected outcomes of this activity are increased participant knowledge and skills in using computer-based accounting software, increased student readiness for the world of work, and increased teacher competence in integrating computerized accounting learning into the teaching and learning process. In addition, this activity is expected to strengthen the synergy between universities and schools in supporting the development of human resources that are adaptive to the development of digital technology in the field of accounting.